The Influence of Current Ratio (CR), Return of Assets (ROA), Company Size and Sales Growth on Capital Structure in Companies Registered on JII for the 2015-2021 Period - Sheila Chairunnisa Dewi; Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the effect of the Current Ratio (CR), Return Of Assets (ROA), Company Size (size) and Sales Growth (Growth) on the Capital Structure of companies listed on JII for the 2015-2021 period. The sample in this study were 10 companies. The data used in this study comes from secondary data obtained from the company's financial statements. Related to data analysis, this study uses linear regression analysis of panel data with the Random Effect Model (REM) model. It is known that the results obtained in this study are Current Ratio (CR) having a negative and significant effect on capital structure by proxies Debt to Equity Ratio (DER), Return Of Assets (ROA), and Firm Size having a positive and significant effect on capital structure by Debt to Equity Ratio (DER) proxy and Sales Growth has no effect on capital structure. Therefore, companies can increase their Current Ratio (CR), Return Of Assets (ROA), and Company Size so that the company's capital structure can be used optimally and efficiently.